The Induction of Dissociative States: A Meta-Analysis - Brake, Benjamin; Wieder, Lillian; Hughes, Natasha; Lalinde, Ivonne Saravia; Marr, Danielle; Geagea, Dali; Pick, Susannah; Reinders, Antje A.T.S.; Kamboj, Sunjeev K.; Thompson, Trevor; Terhune, Devin B. (Biological Psychiatry Global Open Science, 2025)
Background: Dissociative states, characterized by discontinuities in awareness and perception, occur in a diverse array of psychiatric disorders and contexts. These states have been experimentally modeled in the laboratory through various induction methods, but relatively little is known about the efficacy and comparability of different experimental methods. Methods: In this meta-analysis, we quantified dissociative states, as indexed by a standardized instrument (Clinician-Administered Dissociative States Scale), at baseline in varied diagnostic categories and in response to different experimental induction methods (psychological techniques and pharmacological agents) in both clinical and nonclinical samples. Primary outcomes were state dissociation effect sizes (Hedges’ g) (PROSPERO registration: CRD42022384886). A total of 2214 articles were screened, which yielded 123 eligible articles and 155 effect sizes comprising 6692 individuals. Results: High levels of baseline state dissociation were observed in multiple diagnostic categories relative to controls, with the largest effects found in the dissociative and complex subtypes of posttraumatic stress disorder (PTSD-DC). In controlled experiments, induced state dissociation was most pronounced in response to mirror gazing and multiple pharmacological agents, with effects in ketamine and cannabis exceeding baseline state dissociation in PTSD-DC. The effect sizes were characterized by pronounced heterogeneity but were not reliably associated with methodological features of the original studies. Conclusions: Elevated state dissociation is present in multiple diagnostic categories, and comparable or higher levels can be reliably induced in controlled experiments using psychological techniques and pharmacological agents. These results demonstrate the efficacy of several methods for experimentally modeling dissociation and have implications for measuring adverse events and predicting outcomes in clinical interventions that involve pharmacological agents.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Dissociative; Ketamine; Mirror gazing; NMDAR; Psychedelics; PTSD